Advances in applied supramolecular technologies. (13th January 2021) - Williams, George T.; Haynes, Cally J. E.; Fares, Mohamed; Caltagirone, Claudia; Hiscock, Jennifer R.; Gale, Philip A.
Abstract : Supramolecular chemistry has successfully built a foundation of fundamental understanding. However, with this now achieved, we show how this area of chemistry is moving out of the laboratory towards successful commercialisation. Abstract : Supramolecular chemistry is a comparatively young field that to date has mainly been focused on building a foundation of fundamental understanding. With much progress in this area, researchers are seeking to apply this knowledge to the development of commercially viable products. In this review we seek to outline historical and recent developments within the field of supramolecular chemistry that have made the transition from laboratory to market, and to bring to light those technologies that we believe have commercial potential. In doing so we hope we may illuminate pathways to market for research currently being conducted.